Antifungal Drugs in the Management of Hematological Diseases in a Home Care Program. (December 2013) - Tendas, Andrea; Cupelli, Luca; Trawinska, Malgorzata Monika; Lentini, Raffaello; Giovannini, Marco; Scaramucci, Laura; Perrotti, Alessio; de Fabritiis, Paolo; Niscola, Pasquale
Antifungal drugs are frequently used in hematology due to relatively high frequency of infections. Electronic health records of home care patients were retrospectively scanned, looking for antifungal drugs, nystatin, fluconazole, amphotericin B, caspofungin, itraconazole, voriconazole, and posaconazole; we extrapolated frequency, type, indication for use, and duration of each identified antifungal treatment. From September 15, 2011 to September 15, 2012, among 106 patients, median age 83 years, affected by cancer in 82 and other diagnosis in 24 patients, 18 were treated with antifungals, 12 with systemic antifungal (fluconazole 6, itraconazole 5, sequential voriconazole, and itraconazole 1) and 6 with local antifungal. According to our results, the use of antifungals in home care hematological patients is frequent, but limited to certain molecules.